EFEKTIVITAS PENGUATAN PENGELOLAAN DANA DESA DALAM MENINGKATKAN PERTUMBUHAN EKONOMI BERKELANJUTAN DI KABUPATEN SIMALUNGUN - Ruth Tridianty Sianipar; Juan Anastasia Putri; Ady Inrawan; hery silitonga; Lenny Dermawan Sembiring (Politeknik Ganesha Medan, 2023)
The purpose of this study was to analyze the effectiveness of managing village funds in increasing sustainable economic growth in Simalungun Regency. This research method uses a research design with a qualitative approach. The subject of this research is a village in Simalungun Regency. The research was carried out in four sub-districts in Simalungun Regency in Panombeian Pane, Panei, Siantar, Tanah Jawa, and Sidamanik sub-districts in 80 villages. Data collection techniques using observation, interviews, questionnaires and documentation. The data analysis method used is descriptive qualitative analysis and different test. The research results obtained by respondents stated that village funds channeled from the government were sufficient for village development, in community empowerment village funds were mostly used for village government programs to empower village communities, the village government compiled planning documents consisting of APBDes, RPJMDes, and RKPDes, each program planning must be supported by the village community in its implementation by informing every expenditure and income of funds, supervision conducting regular monitoring related to village physical development, and submission of reports on the use of village funds used for village development need to be submitted transparently